Penggunaan Acidifier sebagai Feed Additive dalam Pakan yang Mengandung Probiotik terhadap N-NH3 dan Kadar Air Feses Ayam Broiler - Aulia Rizaldi Hafiz Hakim; Efka Aris Rimbawanto; Bambang Hartoyo (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. This study aimed to determine the most effective acidifier to be combined with a probiotic-supplemented diet on lowering the level of N-NH3 and water content in broiler chicken feces. Materials and methods. This study was conducted from September 27 to October 31, 2019. The maintenance of chickens was conducted in experimental farm, while N-NH3 and water content analysis was performed in the Laboratory of Animal Feed and Nutrition Sciences, Faculty of Animal Science, Universitas Jenderal Soedirman, Purwokerto. Experiment was conducted in-vivo with 4 treatments (R0 = basal feed; R1= basal feed + lactic acid; R2= basal feed + citric acid; R3= basal feed + formic acid) and 5 repetitions. Each type of acidifier was mixed in drinking water at a concentration of 1% of chicken body weight. The significant results were further analyzed using HSD (honestly significant difference) test. Results. Results of this study showed the average levels of N-NH3 ranged from 0.252 ppm – 0.266 ppm and water ranged from 43.93% – 47.83% were contained in chicken feces. However, statistical analysis showed that the results were not significantly different compared to the control group. It can be concluded that three types of acidifier (citric acid, lactic acid, and formic acid) are able to increase the growth of probiotics and decrease the pathogenic bacteria in digestive track of broiler chicken. Conclusion. That condition is caused by low deamination that can be indicated by low levels of N-NH3 and water content of feces.